Terpaan Media Sosial Terhadap Konsentrasi Belajar Anak: Studi Kasus di Desa Tegalrejo Kecamatan Mayang Kabupaten Jember - Wahidi, Ach.; Baidawi (Jisab, 2023)
In this very modern era, technological developments continue to grow, because technological developments will go according to the development of increasingly high science. Technology was created to provide convenience for human life in carrying out daily activities and provide positive but also negative values. Social media plays a very important role in people's lives. This study aims to determine social media exposure to children's learning concentration in Tegalrejo Village, Mayang District, Jember Regency. This study used a qualitative approach and descriptive data analysis. This qualitative research was conducted by emphasizing the depth of the concept studied empirically. This qualitative research was conducted by collecting data in the form of observation notes, interview notes, field documentation, photographs and other supporting data. The results of the study prove that the existence of social media greatly interferes with children's learning concentration, especially in the village of Tegalrejo, Mayang District, Jember Regency.